VARIATION-DIFFERENCE SCHEMES ON COORDINATE CONDENSED GRIDS FOR BIHARMONIK EQUATION - Dadayan, Ye. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
The paper is devoted to the study of behavior of the solution of first boundary problem for biharmonik equation in the neighborhood of angular point. It is proved that the solution of the problem can be represented in a certain form, which allows constructing variation-difference schemes on non-regular grids. Exact estimations for convergence rate are obtained.